Superconducting transition in YBCO bulk ceramics: correlating sintering temperature, phase formation, and ac susceptibility (peralihan superkonduktor dalam seramik pukal YBCO: menghubungkaitkan suhu pensinteran, pembentukan fasa dan kecenderungan ac) - Mohamed Arebat, Ryad Alhadei; Awang Kechik, Mohd Mustafa; Chen, Soo Kien; Lim, Kean Pah; Hoo, Keong Peh; Shaari, Abdul Halim (Penerbit Universiti Kebangsaan Malaysia, 2025)
Sintering significantly influences the phase composition and crystal structure of high-temperature superconductors, such as yttrium barium copper oxide (YBa2Cu3O7-δ, YBCO) bulk ceramics, thereby impacting their superconductivity. This study investigates the effects of various sintering temperatures (920 °C, 950 °C, and 980 °C) on phase formation, AC susceptibility, and the superconducting transition temperature (Tc) in pure YBCO bulk ceramics synthesized via traditional solid-state reaction method (SSR). Characterization techniques employed include X-ray diffraction (XRD), AC susceptibility (ACS), and temperature-dependent resistance measurements via the four-point probe method (4PP). XRD analysis confirmed the predominance of the YBCO phase across all samples, with the highest phase purity (98.9%) and optimal oxygen content achieved at 980 °C. The superconducting transition temperature Tc-onset measured by ACS for the sample sintered at 980 °C was 93.21 K, while 4PP yielded a Tc-onset of 91.28 K; both values decreased at lower sintering temperatures. Notably, the superconducting transition width (ΔTc) narrowed with increasing sintering temperature, with the sharpest transition observed at 980 °C, indicating enhanced phase homogeneity and intergranular connectivity. Additionally, the critical current density (Jcm) at the peak temperature (Tp) of the imaginary part (χ’’) was calculated using the Bean critical state model, revealing a maximum Jcm of 7.639 A/cm2 for the sample sintered at 980 °C.